Positive Effects of Science and Technology Summer Camps on Confidence, Values and Future Intentions - Crombie, Gail; Walsh, John P.; Trinneer, Anne (Canadian Journal of Counselling and Psychotherapy, 2007)
The purpose of this study was to evaluate the effects of science and technology summer camps on the confidence, values, and future intentions of female and male campers. The week-long camps were administered by Actua, a national organization with a mandate to increase awareness of science and technology among Canadian youth. Campers completed a survey both pre- and post-camp. Camps were perceived to be a very positive experience by 83% of campers. Significant positive changes were reported in confidence, values, and future intentions. Results provide some of the first quantitative evidence, at a national level, for the effectiveness of science and technology summer camps that use a hands-on, interactive approach.